2016
DOI: 10.15390/eb.2016.4595
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Reading Attitudes and Preferences between Gifted and Non-gifted Elementary Students

Abstract: Öğrencilerin akademik ihtiyaçlarını daha iyi karşılayabilmek için, onların yetenek, tutum ve tercihlerini daha iyi anlamaya ihtiyaç vardır. Bu çalışmanın temel amacı üstün zekalı olan ve üstün zekalı olmayan öğrencilerin okuma tutumları ve tercihleri arasındaki farkları ortaya çıkarmaktır. Bu amaca ulaşabilmek için nicel araştırma yöntemi kullanılmıştır ve sayısal veriler kesitsel tarama yoluyla toplanmıştır. Yapılan MANOVA analizi sonucunda üstün zekalı olan ve üstün zekalı olmayan öğrencilerin akademik ve di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 16 publications
(13 reference statements)
1
3
0
Order By: Relevance
“…They crafted representations that extended understanding of the text. Their representations were similar to what Bahar et al (2016) revealed about gifted students’ ability to interpret both text and visual information through their preference for comic books.…”
Section: Discoveriessupporting
confidence: 73%
See 3 more Smart Citations
“…They crafted representations that extended understanding of the text. Their representations were similar to what Bahar et al (2016) revealed about gifted students’ ability to interpret both text and visual information through their preference for comic books.…”
Section: Discoveriessupporting
confidence: 73%
“…Finally, Bahar et al (2016) studied differences in reading attitudes between gifted and nongifted students. They discovered that there were no differences in attitudes about academic and recreational reading.…”
Section: Why Literature Circlesmentioning
confidence: 99%
See 2 more Smart Citations